Postmodern Ambivalence of Identities, Moralities and Law(lessness): The Detective-Criminal Continuum in Caleb Carr’s The Alienist - Muhammad Furqan Tanvir; Dr. Waseem Anwar; Dr. Amra Raza (Journal of Research in Humanities, 2019)
Ajoka Theatre’s Barri/The Acquittal underscores one major trend in post-colonial writing, that is, the prison theater, which in Gary Boire’s view, revolves “parodically around such mechanisms of authority as trial and judgment, discipline and imprisonment.” This paper examines the features employed by Shahid Nadeem in Barri that also characterize the postcolonial prison theatre which are: Foucault’s illustration of the basic methodology of the body as text, the reversal of the fool’s festival, the scapegoat ritual, a mocking mime, folk humor which mimics official ceremonies, etc.” It also appropriately fits into the category of the carnivalesque described by Bakhtin, a form which directly disrupts all forms of official authority and systems of hegemony and totalitarian control, which is another aspect of postcolonial prison theatre. The Acquittal/ Barri graphically paints the abject conditions of Pakistani prisons and their inmates. Nadeem unveils the inhuman and derogatory treatment inflicted on women in prisons, exposing simultaneously the circumstances and forces that are involved in bringing them to this deplorable state. The play also focuses on the patterns of torture designed specifically for female prisoners, and the way female prisoners interact with each other, and their gradually developing collective feminine consciousness. Simultaneously, the very coercive system also reveals the gaps and fissures that allow for expressions of freedom and transgression. Barri dissects and carves out the body of ideology that helps shape systems of control, exhibiting dramaturgies of freedom or rebellion against authority. The paper explores how the play weaves out patterns of feminist theatre and the postcolonial prison theatre that are affiliated in nature and aesthetics.